2011
DOI: 10.1128/aem.06711-11
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Correlation between Virus Barosensitivity and the Presence of a Viral Envelope during Inactivation of Human Rotavirus, Vesicular Stomatitis Virus, and Avian Metapneumovirus by High-Pressure Processing

Abstract: High-pressure processing (HPP) is a nonthermal technology that has been shown to effectively inactivate a wide range of microorganisms. However, the effectiveness of HPP on inactivation of viruses is relatively less well understood. We systematically investigated the effects of intrinsic (pH) and processing (pressure, time, and temperature) parameters on the pressure inactivation of a nonenveloped virus (human rotavirus [HRV]) and two enveloped viruses (vesicular stomatitis virus [VSV] and avian metapneumoviru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 53 publications
3
39
0
Order By: Relevance
“…Interestingly, HPP inactivation of the Wa strain was not significantly impacted by the initial temperature during treatment in culture medium or oyster tissues. This is consistent with our previous observation of an approximately a 5-log virus reduction for the Wa strain under 400 MPa at either 4 or 20°C (27). Overall, our results suggest that a low initial temperature increases the inactivation of a majority of the RV strains by HPP.…”
Section: Rv Is a Major Cause Of Infant Gastroenteritis And Death Worlsupporting
confidence: 82%
See 2 more Smart Citations
“…Interestingly, HPP inactivation of the Wa strain was not significantly impacted by the initial temperature during treatment in culture medium or oyster tissues. This is consistent with our previous observation of an approximately a 5-log virus reduction for the Wa strain under 400 MPa at either 4 or 20°C (27). Overall, our results suggest that a low initial temperature increases the inactivation of a majority of the RV strains by HPP.…”
Section: Rv Is a Major Cause Of Infant Gastroenteritis And Death Worlsupporting
confidence: 82%
“…RV plaque assay was performed as described previously (27). Briefly, monolayers of MA-104 cells were grown in six-well plates (Corning Life Sciences, Wilkes-Barre, PA) at a density of 2 ϫ 10 6 cells per well.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, greater than 2 log unit reductions of the RNA copy numbers could be achieved for HuNoV GI.1 and GII.4. HHP mainly targets the capsids and not the genomes of the viruses (22,30,31). A previous study has shown that HHP disrupts the structure of the viral capsid of MNV-1 and not the primary or secondary structure of the VP1 protein, which plays a role in viral attachment (22).…”
Section: Discussionmentioning
confidence: 99%
“…High-pressure processing (HPP) has come to the forefront as a promising intervention for viral inactivation in foods since it has been reported to effectively inactivate some foodborne viruses (such as hepatitis A virus and rotavirus), prevent internalization of particles, and inactivate both surface-contaminated and internalized particles (11,13,(15)(16)(17). In recent years, HPP has been used to treat high-risk foods for virus contamination, including fruit and vegetable product categories (e.g., salsa, apple sauce, and various fruit blends and purees) and shellfish (e.g., oysters and clams).…”
mentioning
confidence: 99%